Social media influence on politicians' and citizens' relationship through the moderating effect of political slogans - Fatema, Shafaq; Yanbin, Li; Fugui, Dong (Frontiers in Communication, 2022)
The digitalization of communication means has revolutionized the way people observe and react to the social and political developments in their surroundings. Rapidly growing influence of social media prompted this exploratory research article of utilizing social networking sites by politicians to build a cordial and strong relationship with the common citizens. This article focuses on investigating social media’s influence on relationship between politicians and citizens through the moderating effect of political slogans. Social media not only enable politicians to directly communicate with the citizens but also encourages political participation of citizens in the form of feedback via comments on social networking sites. Political slogans play a significant role in image building of a particular political force in the eyes of citizens. Quantitative analysis approach is utilized in research article. Data is collected via survey questionnaire from a variety of social media users with cross-sectional time horizon. Convenience sampling method is utilized in data collection across two cities of Pakistan. Smart PLS 3 has been used for hypothesis testing. The effect of the Moderator i.e., Political Slogans of the basic four Political Parties of Pakistan are measured individually. Results depict that the impact of Social Networking Sites and Politics on Politician & Citizens relationship is positive and significant. This research article can be a stepping stone for further related research to enable Politicians to make positive relationships with citizens by effectively utilizing the social media platform.